2018
DOI: 10.1007/s00223-018-0444-y
|View full text |Cite
|
Sign up to set email alerts
|

The C-Terminal Intact Forms of Periostin (iPTN) Are Surrogate Markers for Osteolytic Lesions in Experimental Breast Cancer Bone Metastasis

Abstract: Periostin is an extracellular matrix protein that actively contributes to tumor progression and metastasis. Here, we hypothesized that it could be a marker of bone metastasis formation. To address this question, we used two polyclonal antibodies directed against the whole molecule or its C-terminal domain to explore the expression of intact and truncated forms of periostin in the serum and tissues (lung, heart, bone) of wild-type and periostin-deficient mice. In normal bones, periostin was expressed in the per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…Finally, cathepsin K was demonstrated to cleave periostin, which may be linked to breast cancer bone metastasis. The decrease of C-terminal intact periostin was namely shown to be a marker for osteolytic lesions in breast cancer bone metastasis and could be used to detect bone relapse in patients [89]. Cathepsin K cleavage of osteonectin was also implicated in experimental prostate to bone tumor metastasis, where both the protease and substrate expression levels were higher.…”
Section: Ecm Proteolysis and The Cathepsinsmentioning
confidence: 99%
“…Finally, cathepsin K was demonstrated to cleave periostin, which may be linked to breast cancer bone metastasis. The decrease of C-terminal intact periostin was namely shown to be a marker for osteolytic lesions in breast cancer bone metastasis and could be used to detect bone relapse in patients [89]. Cathepsin K cleavage of osteonectin was also implicated in experimental prostate to bone tumor metastasis, where both the protease and substrate expression levels were higher.…”
Section: Ecm Proteolysis and The Cathepsinsmentioning
confidence: 99%
“…Postn has been suggested as a biomarker of numerous bone conditions including cortical bone metabolism [ 19 ], chondrosarcoma [ 58 ], arthritis [ 38 ], fibrous dysplasia of bone severity [ 59 ], and a surrogate marker for osteolytic lesions in breast cancer [ 60 ]. Postn is a good marker of cortical porosity [ 61 ], as its serum concentration increases with cortical porosity in conditions of mechanical stress under gravity.…”
Section: Resultsmentioning
confidence: 99%
“…OS is clinically characterized by extensive bone destruction and metastasis in which osteoclasts play essential roles (23)(24)(25)(26). It was reported that osteoclasts are responsible for bone destruction and metastasis in bone metastases (5). Herein, osteoclast could be a target both in bone destruction and cancer progression.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it is urgent to explore new targets for OS therapies (4). It is well established that osteoclasts are responsible for bone destruction in cancer bone metastasis such as breast cancer and prostate cancer and this is necessary for tumor expansion within the bone (5)(6)(7). And in OS progression, osteoclasts are believed to play a crucial role.…”
Section: Introductionmentioning
confidence: 99%